Effects of Synthetic Astaxanthin on the Growth Performance, Pigmentation, Antioxidant Capacity, and Immune Response in Black Tiger Prawn (Penaeus monodon) - Qiang Chen; Shuting Huang; Jieyu Dai; Congcong Wang; Songming Chen; Yuanxin Qian; Yangyang Gong; Tao Han (Aquaculture Nutrition)
Synthetic astaxanthin is an effective nutritional strategy for improving shrimp body color and promoting growth. However, the optimal amount of astaxanthin in feed also varies with the synthetic technology and purity. In the present study, five diets containing different doses of synthetic astaxanthin (0% (CON), 0.02% (AX0.02), 0.04% (AX0.04), 0.08% (AX0.08), and 0.16% (AX0.16)) were administered to Penaeus monodon (initial body weight: 0.3 ± 0.03 g) for 8 weeks. With an increase in astaxanthin content in feed, weight gain and specific growth rate increased initially and subsequently decreased, with the highest value appearing at AX0.08. Dietary astaxanthin supplementation obviously improved the carapace and muscle color by enhancing astaxanthin pigmentation. Meanwhile, the fatty acid profile was altered by dietary astaxanthin, as evidenced by a decline in palmitic acid proportion, along with an increase in n-3 polyunsaturated fatty acids (n-3 PUFA) contents in muscle. In addition, dietary astaxanthin supplementation regulated prawn’s antioxidant capacity. In the hemolymph, the activities of glutamic pyruvic transaminase (GPT) showed a significantly decrease trend with linear effect. The activities of glutamic oxaloacetic transaminase (GOT) and the contents of malondialdehyde (MDA) were first downregulated and then upregulated with significantly quadratic pattern. In the hepatopancreas, the activities of superoxide dismutase (SOD) and the contents of MDA were significantly downregulated with the increase of dietary astaxanthin levels. Reduced glutathione (GSH) contents and catalase (CAT) activities were also significantly decreased in group AX0.08. Correspondingly, astaxanthin decreased GSH and MDA contents under transportation stress. Moreover, the mRNA expression of immune genes (traf6, relish, and myd88) were inhibited by dietary astaxanthin supplementation. Based on the results of polynomial contrasts analysis and Duncan’s test, dietary synthetic astaxanthin is a suitable feed additive to improve the growth, body color, antioxidant capacity, and nonspecific immunity of P. monodon. According to the second-order polynomial regression analysis based on the weight gain, the optimal supplementation level of dietary astaxanthin was 90 mg kg−1 in P. monodon.